DemTect: a new, sensitive cognitive screening test to support the diagnosis of mild cognitive impairment and early dementia. - Kalbe, E; Kessler, J; Calabrese, P; Smith, R; Passmore, A P; Brand, M; Bullock, R (International Journal of Geriatric Psychiatry, 2004)
To design a new, highly sensitive psychometric screening to identify patients with mild cognitive impairment (MCI) and patients with dementia in the early stages of the disease. Five tasks were included in the DemTect: a word list, a number transcoding task, a word fluency task, digit span reverse, and delayed recall of the word list. The normation was performed with 145 healthy control subjects (CG). Furthermore, 97 MCI patients and 121 patients with possible Alzheimer's disease (AD) were tested with the DemTect and the MMSE. Classification rates for both tests were analysed. On the basis of the CG data, age-dependant transformation algorithms for the DemTect subtests were defined, and an education correction was provided for the total transformed score. The patient groups scored significantly below the CG in both the DemTect and the MMSE. Compared to the MMSE, classification rates of the DemTect were superior for both the MCI and the AD group, with high sensitivities of 80% and 100%, respectively. The DemTect is short (8-10 minutes), easy to administer, and its transformed total score (maximum 18) is independent of age and education. The DemTect helps in deciding whether cognitive performance is adequate for age (13-18 points), or whether MCI (9-12 points) or dementia (8 points or below) should be suspected.